A multifunctional composite Fe3O4/MOF/l-cysteine for removal, magnetic solid phase extraction and fluorescence sensing of Cd(ii). Issue 19 (16th March 2018) - Fan, Lu; Deng, Min; Lin, Caixue; Xu, Chen; Liu, Yana; Shi, Zhennan; Wang, Yingxi; Xu, Zushun; Li, Ling; He, Man
Abstract : Fe3 O4 /MOF (metal organic framework)/l -cysteine was synthesized and applied for the removal of Cd(ii ) from wastewater. Abstract : Fe3 O4 /MOF (metal organic framework)/l -cysteine was synthesized and applied for the removal of Cd(ii ) from wastewater. The adsorption kinetics and isotherms were investigated, and the results indicated that the adsorption obeyed the pseudo-second-order kinetic model and Langmuir isotherm. The maximum adsorption capacity was calculated to be 248.24 mg g −1 . Fe3 O4 /MOF/l -cysteine was further applied to determine trace amounts of Cd(ii ) in real water samples using ICP-AES (inductively coupled plasma-atomic emission spectroscopy) based on magnetic solid-phase extraction (MSPE). The determination limit was 10.6 ng mL −1 . Additionally, Fe3 O4 /MOF/l -cysteine can also be used as a fluorescent sensor for "turn-off" detection of Cd(ii ), and the detection limit was 0.94 ng mL −1 .